Implementasi Nilai-Nilai Moderasi Beragama Melalui Kegiatan Festival Anak Bangsa di Desa Pekebunan Membang Muda - Syavina Nadhira Lubis; Nabila Zahara; Rohid Akbar; Revi Febrian; Nadya Nurhanifa; Ahmad Sampurna (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2025)
This study discusses the implementation of religious moderation values through the Festival Anak Bangsa held in the Pekebunan Membang Muda Village. The festival was initiated by students from the Kuliah Kerja Nyata (KKN) UINSU with the aim of instilling tolerance, inclusiveness, and harmony among villagers from diverse religious and cultural backgrounds. The research method used is a descriptive qualitative approach with observation of 204 participants from various age groups, ranging from children to adults. The research findings indicate that the Festival Anak Bangsa is effective in instilling religious moderation values such as balance in faith, firmness in religious principles, tolerance toward differences, and equality among religious communities. The event involved various educational competitions emphasizing values of togetherness and cooperation, engaging all participants. Additionally, the involvement of religious leaders, village government, and the community played a key role in the success of the event and in conveying messages of religious moderation in a direct and comprehensive manner. The festival successfully created a strong social harmony atmosphere in the Pekebunan Membang Muda Village, strengthening the bond among villagers regardless of their religious background or age. The Festival Anak Bangsa not only served as a recreational event but also as an effective medium to raise awareness about the importance of living peacefully and respecting diversity. This study underscores the role of cultural and social activities in strengthening tolerance and harmony among citizens in a pluralistic society.